A two-rule analysis of measure noun phrases - Flickinger, Dan; Bond, Francis (Proceedings of the 10th International Conference on Head-Driven Phrase Structure Grammar, 2003)
In this paper we present an analysis of English measure noun phrases. Measurenoun phrases exhibit both distributional idiosyncrasy, in that they appear inpositions normally filled by degree adverbs: "a ten inch long string"; andagreement discord: "ten inches is enough", "it is ten inch/*inches long".The analysis introduces one idiosyncratic construction, the Measure PhraseRule, which links together syntax and inflectional morphology. Combined withexisting rules, in particular the Noun-noun Compound Rule, the new ruleaccounts for the both the distributional and agreement idiosyncrasies. Therule has been implemented and tested in the ERG, a broad-coverage grammar ofEnglish. Our analysis supports the position that broad-coverage grammarswill necessarily contain both highly schematic and highly idiosyncraticrules.